2016
DOI: 10.1155/2016/6901345
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlactatemia and the Outcome of Type 2 Diabetic Patients Suffering Acute Myocardial Infarction

Abstract: Background. Increased lactate production is frequent in unregulated/complicated diabetes mellitus. Methods. Three groups, each consisting of 40 patients (type 2 diabetics with myocardial infarction, DM+AMI, nondiabetics suffering myocardial infarction, MI, and diabetics with no apparent cardiovascular pathology, DM group), were tested for pH, serum bicarbonate and electrolytes, blood lactate, and CK-MB. Results. Blood lactate levels were markedly higher in AMI+DM compared to MI group (4.54 ± 1.44 versus 3.19 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…To our knowledge, AMI is usually associated with the effect of tissue oxygenation, which may be due to insufficient oxygen supply or inhibition of mitochondrial pyruvate dehydrogenase complex. 20 When oxygen supply exceeds the capacity of diseased vessels, hypoxia forces myocardium to change from an aerobic metabolism to an anaerobic metabolism, leading to lactate accumulation. 10 As previously reported, lactate was the strongest predictor as a determinant of global tissue hypoxaemia.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, AMI is usually associated with the effect of tissue oxygenation, which may be due to insufficient oxygen supply or inhibition of mitochondrial pyruvate dehydrogenase complex. 20 When oxygen supply exceeds the capacity of diseased vessels, hypoxia forces myocardium to change from an aerobic metabolism to an anaerobic metabolism, leading to lactate accumulation. 10 As previously reported, lactate was the strongest predictor as a determinant of global tissue hypoxaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to increased basal plasma lactate levels, the postprandial change in lactate following a meal is significantly reduced in T2D. Thus, this reduction in meal-induced lactate response may contribute to postprandial hyperglucagonemia in T2D patients [ 82 ] due to reduced lactate inhibition of GCG secretion. GCG signaling also increases hepatic lactate output [ 83 ] and thus in T2D, elevated GCG levels may contribute to increased lactate levels.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Data from early study demonstrated that metabolic acidosis and lactic acidosis are important factors in causing the high mortality from acute myocardial infarction. 17 However, little data is available on the association of acidemia with short-term mortality of AMI patients. Here, we retrospectively selected 972 AMI patients admitted in intensive care unit (ICU) based on the Medical Information Mart for Intensive Care (MIMIC) III, aiming to detect the association of acidemia with the 30-day mortality and 90-day mortality of AMI patients.…”
Section: Introductionmentioning
confidence: 99%